Nursing workload in specialized Semi-intensive Therapy unit: workforce size criteria - Trettene, Armando dos Santos; Luiz, Aline Godoi; Ribeiro Razera, Ana Paula; Maximiano, Thais de Oliveira; Ravagnani Neves Cintra, Flavia Maria; Monteiro, Laressa Manfio [UNESP] (Univ Sao Paolo, 2015)
Objective: To assess the nursing workload (NW) in Semi-intensive Therapy Unit, specialized in the care of children with Craniofacial anomalies and associated syndromes; to compare the amount of workforce required according to the Nursing Activities Score (NAS) and the COFEN Resolution 293/04. Method: Cross-sectional study, whose sample was composed of 72 patients. Nursing workload was assessed through retrospective application of the NAS. Results: The NAS mean was 49.5%. Nursing workload for the last day of hospitalization was lower in patients being discharged to home (p<0.001) and higher on the first compared to last day of hospitalization (p<0.001). The number of professionals required according to NAS was superior to the COFEN Resolution 293/04, being 17 and 14, respectively. Conclusion: The nursing workload corresponded to approximately 50% of the working time of nursing professional and was influenced by day and outcome of hospitalization. The amount of professionals was greater than that determined by the existing legislation.
Keywords: Workload; Nursing; Nursing Staff; Cleft Lip; Cleft Palate; Intensive Care Units